Preparation and In Vitro-In Vivo Evaluation of Luteolin Loaded Gastroretentive Microsponge for the Eradication of Helicobacter pylori Infections - Mohammed Jafar; Mohammed Salahuddin; Mohd Sajjad Ahmad Khan; Yasir Alshehry; Nazar Radwan Alrwaili; Yazeed Ali Alzahrani; Syed Sarim Imam; Sultan Alshehri (MDPI AG, 2021)
The current study aimed to develop a luteolin gastric floating microsponge for targeting Helicobacter pylori. The microsponge formulations were prepared by a quasi-emulsion method, and then evaluated for various physicochemical variables. The best microsponge was further assessed for drug-polymer interactions, surface morphology, in vivo floating, and in vitro anti H. pylori activity. The formulation which exhibited comparatively good production yield (64.45% ± 0.83), high entrapment efficiency (67.33% ± 3.79), prolonged in vitro floating time (>8 h), and sustained in-vitro drug release was selected as the best microsponge. The SEM study revealed that the best microsponge was spherical in shape and has a porous surface with interconnecting channels. DSC and XRD studies demonstrated the dispersion of luteolin in the polymeric matrix of the microsponge. Ultrasonography confirmed that the best microsponge could in the rat stomach for 4 h. The in vitro MIC results indicate that the anti H. pylori activity of the best microsponge was almost doubled and more sustained compared to pure luteolin. To conclude, it can be said that the developed luteolin gastric floating microsponge could be a better option to effectively eradicate H. pylori infections and the histopathological and pharmacodynamic assessments of our best microsponge can be expected to provide a rewarding outcome.